Enhancing Non-SACU Revenue in Swaziland : Improving Tax Policy and Administration - World Bank (Washington, DC, 2013)
The collapse of Southern African Customs Union (SACU) revenue in 2009 has caused the Government to consider enhancing new sources of revenue in earnest to sustain its development policies. Existing plans that were prepared more than 5 years ago to introduce the Value-Added Tax (VAT) and create a new Revenue Authority (RA) focused on improved compliance are therefore more relevant than ever. This initial preparation provides ample room to rapidly improve both the design of taxes and fees and tax administration to ensure they are in line with both Swaziland's unique policy context and sound economic principles. These principles include: (i) policy and administration harmonization with South Africa so that investors view both countries as offering the same tax benefits and to facilitate the seamless launch of the RA with the benefit of the necessary support from (and partial integration with) South Africa's operations; (ii) the ability to implement reform rapidly given the fiscal emergency; and (iii) the need for simple and resilient policy and administrative designs that are able to cope with limited administrative capacity and a history of out-of-control spending.